Evaluation of the Effectiveness of vitamin D compared to metformin on letrozole Induced Polycystic Ovary Syndrome (PCOS) in Female Rats - Najah Mohammed Kubba, Sara; Razaj Al-Basraw, Fadhel Abdul Jabbar; Hassan Wasfi, Rafid Mohammed Ali (Iranian Journal of Pharmaceutical Sciences, 2025)
Vitamin D is an old supplementation with a new mode of action as an encouraging alternative to current therapies for PCOS, and this research is designed to analyze the ability of vitamin D to rebalance hormonal abnormalities, antioxidant capacity, and ovarian morphology in letrozole-induced rats. Thirty-five female Sprague Dawley rats were used, and then they separated into five groups with seven animals each: the first group received only water, the second group received DMSO, the third group signed as PCOS group, Group IV received metformin, Group V received Topferol (vitamin D). PCOS was induced by administration of a daily dose of 1 mg per weight of letrozole for 21 days; after induction, the animals were treated with metformin and vitamin D for 19 days, and at the end of the experiment blood samples and ovarian tissues were taken for analysis. The results show that vitamin D normalized the estrus cycle in rats, restored the normal follicular development process, decreased the high levels of LH and testosterone, and enhanced the total antioxidant capacity. In conclusion, vitamin D is as effective as metformin in the reduction of several hormonal and biochemical features that are usually associated with PCOS mainly by restoring normal estrus cycle, renovating morphological features and folliculogenesis, and organizing abnormalities in hormone levels; however, it showed superior action regarding the antioxidative effect.